Survival of antibiotic resistant escherichia coli in vacuum-packed keropok lekor: Food safety alert among SME keropok lekor producers - Wan-Hamat H.; Lani M.N.; Hamzah Y.; Alias R.; Hassan Z.; Mahat N.A. (Malaysian Society for Parasitology, 2024)
Indexed by WOS/SCOPUS/ERA